Răspuns :
a-b=862
a:b=5r6
a=5b+6
inlocuim cu a=5b+6
avem
a-b=862
5b+6-b=862
5b-b=862-6
4b=856
b=856:4
b=214
inlocuim cu b=214
avem
a-b=862
a-214=862
a=862+214
a=1076
deci nr sunt
a= 1076
b=214
a:b=5r6
a=5b+6
inlocuim cu a=5b+6
avem
a-b=862
5b+6-b=862
5b-b=862-6
4b=856
b=856:4
b=214
inlocuim cu b=214
avem
a-b=862
a-214=862
a=862+214
a=1076
deci nr sunt
a= 1076
b=214
a-b=862
a:b=5 rest 6
a=5b+6
a-b+862
5b+6b-b=862
5b-b=862-6
4b=856
b=856:4
b=214
a-214=862
a=862+214
a=1076
a:b=5 rest 6
a=5b+6
a-b+862
5b+6b-b=862
5b-b=862-6
4b=856
b=856:4
b=214
a-214=862
a=862+214
a=1076